The Effect of Endorphin Massage on Reducing Back Pain in Third Trimester Pregnant Women - Rini Anggeriani; Sagita Darma Sari; Rinda Lamdayani (Lentera Perawat, 2024)
Every pregnant woman will experience various changes that occur in the first trimester, second trimester and third trimester. One of the discomforts experienced by third trimester pregnant women is musculoskeletal changes that cause pain in the mother's back. Pain therapy can be done pharmacologically and non-pharmacologically. One of the non-pharmacological pain therapies is endorphin massage, which is a light touch or massage technique that can stimulate the body to release endorphin compounds which are pain relievers and can create a feeling of comfort. This study aims to determine the effect of endorphin massage on reducing back pain in third trimester pregnant women. This research method uses pre experiment with pre-test post test one group using the Wilcoxon test and sampling using the total population of 15 pregnant women. The research was conducted in April-May 2023. The results of the study obtained the average value of the pain scale before being given endorphin massage is 4.93, after being given endorphin massage down to 2.60. This shows there is a significant effectiveness of endorphin massage on reducing back pain in third trimester pregnant women. The results of the Wilcoxon sign rank test Z score = -3.529 and p = 0.000 where α = 0.05 then p <0.05 means there is an effect of endorphin massage on reducing the intensity of back pain in pregnant women Trimester III.